Is motion the best medicine? Rethinking knee osteoarthritis through gait analysis - Rastogi, Aavrati; Kalia, Roop B.; Meena, Pradeep K. (International Journal of Research in Orthopaedics, 2026)
A gradual degenerative joint disease, knee osteoarthritis (OA), places an enormous strain on healthcare systems around the world, especially in older people and those with metabolic and biomechanical risk factors. Knee OA causes crippling pain, stiffness, and functional incapacity. It is characterized by the slow deterioration of articular cartilage, subchondral bone sclerosis, osteophyte formation, and persistent synovial inflammation. Because of its intricate pathophysiology and the interaction between systemic inflammation and biomechanical stressors, the disease continues to pose a significant challenge, even with the availability of pharmacologic medicines, intra-articular therapy, and surgical procedures.